Low-Risk Myelodysplastic Syndrome Revisited: Morphological, Autoimmune, and Molecular Features as Predictors of Outcome in a Single Center Experience - Fattizzo, Bruno; Levati, Giorgia Virginia; Giannotta, Juri Alessandro; Cassanello, Giulio; Cro, Lilla Marcella; Zaninoni, Anna; Barbieri, Marzia; Croci, Giorgio Alberto; Revelli, Nicoletta; Barcellini, Wilma (Frontiers in Oncology, 2022)
Low-risk myelodysplastic syndromes (LR-MDS) are a very heterogeneous disease, with extremely variable clinical features and outcome. Therapeutic strategies are still limited and mainly consist of erythropoiesis stimulating agents (ESAs) and transfusion support. The contribution of molecular lesions and of autoimmune phenomena to pathogenesis and clinical course, including leukemic evolution, is a field of open investigation. We analyzed data from a cohort of 224 patients with LR-MDS followed at our center in the last 20 years, focusing on morphological, immunological (anti-platelets and anti-erythrocyte autoantibodies, anti-erythroblast antibodies), and molecular features. Hypoplastic bone marrow was found in 7% of cases correlating with younger age, deeper cytopenia, lower dysplasia, and worse response to ESAs. A marker of autoimmunity was observed in 46% of tested cases, who were younger, with less frequent dysplastic changes, and responded better to ESAs and steroids. Finally, 68% of tested cases displayed at least one somatic mutation, most commonly SF3B1, TET2, ASXL1 and SRSF2, associated with older age, presence of neutropenia and lower response to ESAs. Leukemic evolution (2.2%) was associated with presence of somatic mutations, and survival was favorably related to response to ESAs and transfusion independence. Overall, granular evaluation and re-evaluation are pivotal in LR-MDS patients to optimize clinical management.